The Perfecting of Nature : Reforming Bodies in Antebellum Literature - Doty, Josh (Book collections on Project MUSE., 2020)
"The nineteenth century saw a marked change in how Americans viewed and understood the human corporal form. Cookbook writers drew from physiologists' studies of the nervous pathways between the stomach and the brain to promote their recipes as good for mental health. These new ways of understanding the body reflect how Americans were beginning to see the body's constituent parts as interconnected. From the Transcendentalists' idealized concept of self to the rise of Darwinian Theory after the Civil War, the era and its writers redefined the human body as a deeply reactive and malleable object. In this book, Josh Doty explores the 'plasticity' of the antebellum American body-the body's ability to react and change from interior and exterior forces-and argues that literature helped to shape the cultural reception of these ideas"--